2012
DOI: 10.1071/zo12075
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in natural and introduced island populations of koalas in Queensland

Abstract: Island populations of animals are expected to show reduced genetic variation and increased incidence of inbreeding because of founder effects and the susceptibility of small populations to the effects of genetic drift. Koalas (Phascolarctos cinereus) occur naturally in a patchy distribution across much of the eastern Australian mainland and on a small number of islands near the Australian coast. We compared the genetic diversity of the naturally occurring population of koalas on North Stradbroke Island in sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 50 publications
(19 reference statements)
2
29
0
Order By: Relevance
“…Interestingly, the koalas on St. Bees Island, and other island koala populations, had lower levels of genetic diversity than those from Southeast Queensland where they originated (37). The St.…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, the koalas on St. Bees Island, and other island koala populations, had lower levels of genetic diversity than those from Southeast Queensland where they originated (37). The St.…”
Section: Discussionmentioning
confidence: 94%
“…The leaves koalas eat provide most of their water needs, so this covariate may act as a surrogate for tree condition and leaf moisture content [52,53]. Areas surrounding prominent sources of fresh water in other parts of southeast Queensland, for example North Stradbroke Island, also support relatively high numbers of koalas [54]. Such findings thus provide support for research that suggests extreme events, such as droughts and heatwaves, that affect water availability will have both direct and indirect consequences for koalas and other endothermic species that use evaporative cooling for thermoregulation [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…To date, research based on microsatellite markers has defined the genetic diversity and divergence of koala populations in Queensland, particularly SEQ (Fowler et al, 2000;Houlden et al, 1996c;Lau et al, 2014;Lee et al, 2010;Lee et al, 2013b;Sherwin et al, 2000). In 2010, a comprehensive study of in situ koalas in SEQ (n= 512) determined that genetic diversity is relatively high (HE= 0.69-0.73) within koala colonies in the threatened areas of SEQ (Lee et al, 2010), although by 2013, the same wild koala colonies had decreased in heterozygosity (HE= 0.55-0.67) (Lee et al, 2013).…”
Section: The Assessment Of Individual and Population Genetic Variationmentioning
confidence: 99%
“…determined that there was a substantial amount of genetic diversity (HE= 0.69-0.73) remaining within koala populations in the threatened areas of SEQ (Lee et al, 2010), although by 2013, the same wild koala colonies had decreased in heterozygosity (HE= 0.55-0.67) (Lee et al, 2013b). Further analysis of koalas in the Gold Coast region of SEQ was conducted in 2015, which used the same microsatellite markers to allow for a direct comparison and identified that the koala populations tested maintained a high level of heterozygosity (HE= 0.71-0.73) (Seddon et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation